A study of a karate trial teaching class in a teacher training course − based on students' formative assessment - Kentaro Tai; Shutaro Jinno; Namika Motoshima; Toshiyuki Miyara; Takeru Shima; Miki Suetsugu; Masaki Fumoto; Hiroyuki Imamura (Universidad de León, 2019)
The purpose of this study was to examine the effectiveness of a karate trial teaching class in an initial teacher training course, through students' formative assessment. It involved two case studies of trial teaching classes of karate and that of two other activities, taught by the students of an initial teacher training course. The results were assessed using the Students' Formative Assessment of Physical Education (P.E.) Classes scale. Results showed significant differences between groups in "New discovery" (p<.05) and a trend toward statistical significance in "Skill growth", "Fun Exercise" and "Learning friendly" (p<.10) based on the classes provided by karate and other teaching materials. This implies that karate might have different acute effects on students' learning process in the context of school-level physical education.